Nego-feminism as a strategy to improve access to abortion in sub-saharan Africa - Lalique Browne; Irmine Fleury Ayihounton; Thomas Druetz (BMC, 2024)
Abstract Background Abortion is partially legal in 48 of 54 countries in Sub-Saharan Africa (SSA); however, abortion laws are generally weakly implemented, and evidence suggests that extending abortion rights does not necessarily improve abortion access. Objective Reflecting on the implementation challenges faced by the laws extending rights to abortion in SSA, and enriching this approach by considering complementary avenues to overcome barriers in access to abortion. Argument Reproductive justice is a theory that emphasizes the importance of contexts and different levels of societal forces in shaping reproductive freedom. From a reproductive justice perspective, we suggest that the successful implementation of abortion laws is hampered by discrepancies between legal frameworks and socio-cultural contexts in many SSA countries. In many SSA contexts, the legalization of abortion has not been accompanied by a modification of socio-cultural contexts regarding abortion. Until these contexts are more receptive to abortion, implementation issues may persist and access to abortion may remain hindered. Since increasing social acceptability of abortion can be a lengthy process, exploring complementary strategies to improve abortion access can be beneficial. Nego-feminism, an African feminist theory rooted in African values of negotiation and relationships, may be an effective strategy to navigate societal forces to improve abortion access, in the meantime, until greater acceptability and enforcement of abortion laws. An illustration of this promising strategy can be found in abortion accompaniment models such as MAMA network which provide safe access to medication abortion in the informal sector. Conclusion Nego-feminism could potentially improve access to abortion in legally and socially restricted settings. However, the continued fight for the legalization of abortion is essential, while using nego-feminism as a complement.